2017
DOI: 10.5114/pjp.2017.71530
|View full text |Cite
|
Sign up to set email alerts
|

Impact of TGF-β1 expression and -509C>T polymorphism in the TGF-β1 gene on the progression and survival of gastric cancer

Abstract: The aim of this study was to examine the expression of TGF-β1 and TGF-β receptor type II (RII) and the impact of the -509C>T single nucleotide polymorphism (SNP) in the gene in relation to clinicopathological factors in gastric cancer (GC). Using immunohistochemistry we investigated 43 patients with GC for expression of TGF-β1 and TGF-β-RII. Consequently, RFLP-PCR was performed to analyze the presence of -509C>T polymorphism in the TGF-β1 gene. We found that 72.1% of GCs had cytoplasmic TGF-β1 expression and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is well-known that there is TGF-β1 expression with high level in cancer cells. Ananiev et al reported that the expression of TGF-β1 in the gastric cancer patients was associated with shorter survival time and rapid progression (29). Generally, TGF-β1 can induce EMT in various cancer cells, such as breast cancer cells, hepatocellular carcinoma and neuroblastoma cells (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that there is TGF-β1 expression with high level in cancer cells. Ananiev et al reported that the expression of TGF-β1 in the gastric cancer patients was associated with shorter survival time and rapid progression (29). Generally, TGF-β1 can induce EMT in various cancer cells, such as breast cancer cells, hepatocellular carcinoma and neuroblastoma cells (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent with these observations, our results indicated a shorter overall survival after operation for the carriers of the T/T-genotype with high-grade glial tumors compared to the carriers of at least one C-allele, although it should be noted that the survival functions did not find statistical significance. Nevertheless, the negative effect of the T-allele on overall patient survival has been reported widely in other types of cancer, such as colorectal [24], non-small-cell lung cancer [27], and gastric cancer [28].…”
Section: Discussionmentioning
confidence: 99%